A Summary of the Best Evidence for Wet Pack Management - Yi L; Chen Y; Hu R (Risk Management and Healthcare Policy)
Liangying Yi,1,2 Yanhua Chen,1,2 Ruixue Hu1,2 1Department of Sterile Processing Nursing, West China Second University Hospital, Sichuan University/West China School of Nursing, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2Key Laboratory of Birth Defects and Related Diseases of Women and Children (Sichuan University), Ministry of Education, Chengdu, Sichuan, People’s Republic of ChinaCorrespondence: Yanhua Chen, West China Second University Hospital, Sichuan University, No. 20, Section 3, South Renmin Road, Chengdu, Sichuan, 610041, People’s Republic of China, Email 402888515@qq.comBackground: Wet pack after steam sterilization of medical devices in healthcare facilities are unacceptable.Purpose: To retrieve, evaluate and integrate the best evidence related to wet pack management.Methods: We searched the JBI, Up To Date, BMJ, National Guideline Clearinghouse (NGC), National Institute for Health and Care Excellence (NICE), Scottish Intercollegiate Guidelines Network (SIGN), Cochrane library, PubMed, Guideline International Network (GIN), AORN Journal, and other databases using the pyramid “ 6S” model for guidelines, expert consensus, systematic reviews, evidence summaries, decisions, recommended practices, and technical reports on wet pack management. The period of the literature search is from the establishment of the database to January 2024. Two researchers evaluated the literature quality independently, and evidence was extracted from the literature that met the quality standards. AGREE II assessment system, Cochrane bias risk assessment, and JBI Evidence-Based Health care center authenticity assessment were used as the literature evaluation criteria and the JBI 2014 edition evidence pre-grading system for intervention studies. For all types of research, the literature quality and evidence level was evaluated, extracted, and summarized according to the theme.Results: Based on the inclusion criteria, seven pieces of literature were selected, including three guidelines, three randomized controlled trials, and consensus from an expert. Twenty pieces of evidence were obtained from seven different aspects: device packaging stage, loading stage, sterilization stage, unloading and cooling stage, distribution stage, wet package evaluation and analysis, and personnel training.Conclusion: This study summarizes the best evidence on wet pack management and can provide a reference for staff practices in disinfection supply centers to reduce the incidence of wet packs.Keywords: wet pack, prevention, management, evidence-based nursing, summary of evidence